Effect of vitamin D supplementation on body composition, lipid profile, and glycemic indices in patients with obesity-associated metabolic syndrome: a systematic review and meta-analysis - Lili Ge; Shi Gao; Najaf Kia; Yanzhong Wang; Liqun Hua (Diabetology & Metabolic Syndrome)
Abstract Background Vitamin D deficiency is common among individuals with obesity and metabolic disorders. Evidence on its effect on metabolic markers remains inconclusive. This systematic review and meta-analysis aimed to evaluate the impact of vitamin D supplementation on lipid profile, glycemic control, and anthropometric indices. Methods A comprehensive search of PubMed, Embase, Cochrane Library, Web of Science, and China Knowledge Network was conducted from inception to May 2024. Randomized controlled trials (RCTs) evaluating oral vitamin D supplementation in adults with overweight, obesity, or metabolic disorders were included. Weighted mean differences (WMDs) and 95% confidence intervals (CIs) were calculated using a random-effects model. Results Twenty-five RCTs (30 arms) were included. Overall, vitamin D supplementation did not significantly affect triglycerides (TG), total cholesterol (TC), HDL-C, LDL-C, fasting plasma glucose (FPG), insulin, HOMA-IR, HbA1c, waist circumference (WC), or body weight (p < 0.05). Subgroup analyses showed significant effects in certain populations, such as increased HDL-C in individuals with diabetes and elevated LDL-C in younger adults and males. A significant reduction in BMI was observed after adjusting for publication bias (p < 0.05). Heterogeneity varied across outcomes, and risk of bias was generally low, although some studies had unclear reporting. Conclusion Vitamin D supplementation has limited effects on metabolic and anthropometric markers in adults with obesity or related metabolic disorders. Certain subgroups may benefit, warranting further targeted research.